RESPON MASYARAKAT TERHADAP PELAKSANAAN PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) PT. BTN (BINTARA TANI NUSANTARA) DI JORONG AIR RUNDING KEC. KOTO BALINGKA KAB. PASAMAN BARAT PROV. SUMATERA BARAT - Jekki Efrizon; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Corporate Social Responsibility (CSR) is a commitment of the corporation or business world to contribute to sustainable and economic development by paying attention to corporate social responsibility and focuses on the balance between economic, social and environmental aspects.  This research was conducted at  Jurong Air Runding, Koto Balingka, West Pasaman, Province of West Sumatra.  This study was aimed to determine the public responses to the implementation of the Corporate Social Responsibility (CSR) program.  This study used a descriptive quantitative method with a sampling technique in this study used a simple random sampling technique in which respondents numbered 84 people.  The data collection technique used the method of observation, interview, questionnaire, and documentation.  The results showed that most of the public understood what was meant by Corporate Social Responsibility (CSR) and also knew about the program (CSR) implemented by the company PT BTN (Bintara Tani Nusantara).  The community feels that the company needs to continuously contribute to the community through its Corporate Social Responsibility (CSR) program, although currently programs that have been implemented are still not sustaining from the perspective of increasing skill or training, economic, education, and health.  This refers to the incompatibility of the program with what is really needed by the community.  Keywords: PT. BTN, Responses, CSR, Jorong Air Runding